A Diagnostic Loop-Mediated Isothermal Amplification Method to Distinguish Helicoverpa armigera (Lepidoptera: Noctuidae) From Other Related Species in the New World. Issue 3 (27th May 2020) - Amano, Takayuki; Nomura, Masashi
Abstract: Helicoverpa armigera (Hübner) is a notorious agricultural pest native to the Old World. Recently, its invasion into South and Central America has become a serious problem in the New World. The rapid detection of invasive pests is essential to eradicate them and prevent establishment. However, an extremely similar species, H. zea (Boddie) distributed in the New World makes identification difficult. Helicoverpa armigera and H. zea have only minor differences in male genitalia to separate them morphologically. Both species are attracted to the same pheromone lure, and it takes considerable time and effort to identify them from bulk samples obtained during trap monitoring. Although several molecular approaches based on PCR have been reported, these methods require expensive equipment and are unsuitable for onsite diagnostics. Here, we developed a rapid and convenient diagnostic method based on the loop-mediated isothermal amplification to distinguish H. armigera from related species: H. zea, H. assulta (Guenée), H. punctigera (Wallengren), and Chloridea virescens (Fabricius). The diagnostic method makes it possible to detect H. armigera within 90 min only using simple equipment. The method also worked with mixed DNA templates containing excess DNA from H. zea at the ratio of 1:999 ( H. armigera : H. zea ). This method can be an effective tool for onsite diagnostics during monitoring surveys for invasive H. armigera .